Penerapan Program Ekstrakurikuler Weekend Class Action dalam Meningkatkan Kreativitas Siswa - El-Haris, Fina Tamara; Ratnawati, Rinta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the implementation of the Weekend Class Action extracurricular program in enhancing student creativity at Ma'arif 1 Pamekasan Senior High School. This study used a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. Data analysis employed the Miles and Huberman model. The results indicate that the program successfully enhanced student creativity through the implementation of Multiple Intelligences theory, Self-Determination, constructivism, and the 4C skills (critical thinking, creativity, collaboration, and communication). Supporting factors for the program's success included the principal's commitment, the availability of professional teachers, student enthusiasm, and community participation. Barriers faced included limited funding, student dependence on instructors, and limited time and facilities. The school overcame these obstacles with external loans and the involvement of alums as substitute instructors. In conclusion, this program demonstrates that schools in remote areas are capable of producing quality educational innovations. Keywords: Extracurricular Activities, Educational Innovation, Creativity, Weekend Class Action